Pengungkapan Laporan Keuangan Berbasis Website - Ayu Efendi, Dina, Imronudin, S.E, M.Si, Ph.D (2015)
With the development of internet technology is very quick, communication through the internet has been adopted by business sector as an important tool for providing information. The development of information technology, especially the internet has affected how the presentation of company information so that it appears a media presentation of financial reports through the Internet website called Financial Reporting (IFR). The disclosure of financial reports through the website to serve as a communication medium especially for investors who need information financial statements as consideration for investors. This research aims to analyze the extent to which Real Estate Company and a Property exposing financial reports through the website and analyze the relationship of company size and profitability with Internet Financial Reporting (IFR). The sample used is 39 research company Real Estate and Property that reveal financial reports through the website by 2014. By using purposive sampling methods, sample company grouped with positive profitability criteria and company uncover financial reports through the website. Types of data used in this research is secondary data, which consists of financial reports contained on the website of the company by 2014. Analysis of the method used is descriptive statistics and correlation analysis. The conclusion that can be drawn from this research is the company's size and profitability associated with insignificant Internet Financial Reporting (IFR). IFR conditions characteristic both of the completeness, accuracy, and relevance are on condition of being. Whereas, on the characteristics of transparency are on good shape. Keyword: Internet Financial Reporting (IFR), the Internet, and the level of Disclosure